Classification of breast cancer malignancy using cytological images of fine needle aspiration biopsies - Jeleń, Łukasz; Fevens, Thomas; Krzyżak, Adam (Zielona Góra: Uniwersytet Zielonogórski)
According to the World Health Organization (WHO), breast cancer (BC) is one of the most deadly cancers diagnosed among middle-aged women. Precise diagnosis and prognosis are crucial to reduce the high death rate. In this paper we present a framework for automatic malignancy grading of fine needle aspiration biopsy tissue. The malignancy grade is one of the most important factors taken into consideration during the prediction of cancer behavior after the treatment.
Keywords: automated malignancy grading; FNA grading; SVM; breast cancer grading; Bloom-Richardson